The impact of green urbanization on carbon emissions: The case of new urbanization in China - Li, Yali; Gao, Kangli (Frontiers in Environmental Science, 2022)
Urbanization in developing countries has brought economic growth and industrial development, but at the same time, it has also brought environmental problems, especially increased carbon emissions. Recently, China has promoted a new type of urbanization with the common goal of economic growth and green development, which provides a reference for the sustainable development of urbanization in developing countries. The study focuses on microscopic impact of this new urbanization on carbon emissions, which has received little attention previously. This study takes China as an example, constructs a quasi-natural experiment based on the first batch of new urbanization pilot areas in China, selects panel data of 164 prefecture-level cities from 2010-2019, applies the double difference method(DID) to identify the emission reduction effects of pilot policy on carbon emission (carbon emission intensity and per capita carbon emission), the mechanism of action model is constructed for further analysis, and various robustness tests are conducted. The results show that the new urbanization pilot policy can effectively diminish carbon emissions, and the sensitivity of pilot policy to per capita carbon emissions is greater than the intensity of carbon emissions, and the emission reduction effect of pilot policy of new urbanization tends to be enhanced with the implementation of pilot policy. With the improvement of infrastructure, the upgrading of advanced industrial structure, and the strengthening of environmental regulation, the inhibitory effect of new urbanization construction on carbon emissions tends to be enhanced. Various robustness tests show that green urbanization can effectively lessen carbon emissions, and under the constraint of economic growth rate target, if the government still gives priority to economic development, it is not conducive to the development of green urbanization. Therefore, the green urbanization process needs to be accelerated, infrastructure construction is linked, strict and appropriate environmental controls are adopted, the industrial layout is customized and the advanced industrial structure is promoted.